Factores asociados a la producción de textos escritos en inglés en estudiantes de tercer grado de secundaria en Instituciones Educativas Públicas del distrito de Belén 2023 - Cenepo Jipa, Dioselin Andrea (2024)
The present research aims to elucidate the influence of associated factors on the production of written texts in English among third-grade students in public secondary institutions in the Belén district in 2023. The research employed an explanatory approach with field designs, transactional, contemporary, and multivariable trait. The study population consisted of 669 students, with a stratified sample with proportional allocation of 235. The results indicate that associated factors are in the high category (x = 73.578 out of 100), whereas the production of written texts falls within the beginner category (x̄ = 8.182). In summary, the findings from the non parametric Spearman's Rho test indicate the absence of correlation between the analyzed variables. Consequently, it was unnecessary to conduct a regression analysis, suggesting that there is no significant influence of associated factors on the production of written texts in English.